2005
DOI: 10.1177/004051750507500308
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Cross-Sectional Packing Density of Rotor Spun Yarns

Abstract: Packing density, the fiber distribution in a yarn cross section, can to a great extent influence the properties and quality of the yarn. Thus, the need for precise and concise information about packing density becomes a must for an in-depth understanding of yarn structure and hence yarn mechanics. This paper describes a detailed method for determining packing density. We begin by acquiring yarn cross-sectional images to provide input data for calculating yarn cross-sectional packing density. These data include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 11 publications
3
30
1
Order By: Relevance
“…The maximum packing density is within the yarn radius of 0.031 mm, and then it gradually decreased from its core to its surface, which is very similar to other yarns, such as compact yarns, rotor yarns and Murata Jet Spinning (MJS) yarns. 1,11,16 From Figure 3, it can be shown that the vortex-spun yarn has lower fiber packing density value than that of conventional ring-spun yarn at the yarn center and surface. It may be identified that the radial pressure action on the core fibers of vortex-spun yarn, produced by the high-speed whirled air current, is lower than the radial pressure action on the central fibers of conventional ring-spun yarn, produced by the mechanical twist motion in a triangle zone of spinning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum packing density is within the yarn radius of 0.031 mm, and then it gradually decreased from its core to its surface, which is very similar to other yarns, such as compact yarns, rotor yarns and Murata Jet Spinning (MJS) yarns. 1,11,16 From Figure 3, it can be shown that the vortex-spun yarn has lower fiber packing density value than that of conventional ring-spun yarn at the yarn center and surface. It may be identified that the radial pressure action on the core fibers of vortex-spun yarn, produced by the high-speed whirled air current, is lower than the radial pressure action on the central fibers of conventional ring-spun yarn, produced by the mechanical twist motion in a triangle zone of spinning.…”
Section: Resultsmentioning
confidence: 99%
“…The effective yarn diameter D ef obtained from the fiber packing density distribution was considered as the best value representing the real yarn diameter. 1,11 The effective yarn diameter D ef can be obtained according to the fiber packing density value of 0.15 from the fiber packing density distribution curve. 1 That is, the outer diameter of the radial ring, where the fiber packing density distribution is equal to 0.15, is the effective yarn diameter D ef .…”
Section: Evaluation Of Fiber Packing Density In Yarn Cross Sectionmentioning
confidence: 99%
“…Although some researches are concerned with ideal packing density, but because the yarn structure is quiet disordered (Hearle, Grosberg, & Backer, 1969;Petrulis, 2003), most of the researches are limited to calculating this factor for yarns made of circular fibers (Jiang, Hu, & Cheng, 2005;Neckar, Ishtiaque, & Svehlova, 1988). In this paper, a new method based on image analysis is introduced that does not have any limitation with regard to fiber cross-sectional shape.…”
Section: Introductionmentioning
confidence: 99%
“…In some recent researches, the effect of some variables such as yarn count, twist factor, lap hank, card draft, draft doubling and draft at speed frame, ring frame and rotor and air jet spinning on the fiber packing density has been analyzed (Jiang et al, 2005;Kumar, Ishtiaque, & Salhotra, 2006). Yilmaz, Goktepe, Goktepe, and Kremenakova (2007) have analyzed the effect of type of compact spinning machine on the fiber packing density.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, a number of experiments revealed that the radial packing density of staple yarn is non-uniform. 13–18 Based on the assumption that fibers are arranged in the form of concentric helices in a yarn, Hearle et al. 10 introduced the second approach to analyze fiber packing density by dividing the yarn cross-section into several annular zones.…”
mentioning
confidence: 99%